Effects of Various Fat Levels and Sources on Blood Cholosterol Levels in Rabbits - B.zehra Sarıçıçek; Ali Vaiz Garıpoğlu; Ramazan Amanvermez (Journal of Agricultural Sciences)
n this research it was aimed to determine the effects of different fat sources animal fat and vegetable oil and different fat levels O ` /0, 2.5 °İ. and 5 % on various blood parameters of rabbits. With this aim, 5 different group each of with male and female sub-groups were established Group 1= O % fat, grup 2=2.5 % vegetable oil V0 , group 3= 5 % vegetable oil, group 4= 2.5 % animal fat AF , group 5= 5 % animal fat and animals were allocated into these groups. At the end of the experiment, it was determined that blood parameters LDL-C, total cholesterol, phospolipid, HDL-C, tryglyceride, free cholesterol were influenced by different fat sources and levels at different manner and animal fats increased these blood parameters.